1992
DOI: 10.1007/bf01300380
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged clearance is the primary abnormal reflux parameter in patients with progressive systemic sclerosis and esophagitis

Abstract: The purpose of this study is to determine if frequent reflux events from an incompetent LES or poor clearance from decreased peristalsis is the predominant abnormality in PSS patients with severe reflux esophagitis. Seven patients with both classic manometric findings of PSS and endoscopic findings of esophageal ulcerations and/or Barrett's esophagus were compared to nine patients with similar endoscopic findings but with no evidence of a connective tissue disorder. All patients underwent simultaneous intraeso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0
6

Year Published

1994
1994
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 20 publications
2
30
0
6
Order By: Relevance
“…Barrett’s esophagus has been associated with other motility disorders of the gastrointestinal tract, namely scleroderma [132,133,134] and celiac disease. Severity and extent of reflux has been attributed to the integrity of distal esophageal peristalsis.…”
Section: Relationship Between Barrett’s Esophagus and Other Disordersmentioning
confidence: 99%
See 1 more Smart Citation
“…Barrett’s esophagus has been associated with other motility disorders of the gastrointestinal tract, namely scleroderma [132,133,134] and celiac disease. Severity and extent of reflux has been attributed to the integrity of distal esophageal peristalsis.…”
Section: Relationship Between Barrett’s Esophagus and Other Disordersmentioning
confidence: 99%
“…Severity and extent of reflux has been attributed to the integrity of distal esophageal peristalsis. Murphy et al [133] found a significantly lower number of reflux events, but they were of longer duration when patients with manometric features of scleroderma and endoscopic findings of esophageal ulcerations and/or Barrett’s esophagus were compared to patients with similar endoscopic findings but without an associated connective tissue disorder. Based on their findings, they concluded that decreased smooth muscle peristalsis was attributed to be the primary contributor of esophageal injury in scleroderma.…”
Section: Relationship Between Barrett’s Esophagus and Other Disordersmentioning
confidence: 99%
“…To evaluate the relative importance of these two factors, a recent report employed simultaneous manometry, esophageal pH monitoring, and esophageal scintigraphy to study SSc and non-SSc patients with severe gastroesophageal reflux (36). The SSc group had significantly fewer reflux events than did the non-SSc reflux group (although more than normal controls), but once acid was refluxed, it took substantially longer to clear from the esophagus.…”
Section: The Esophagusmentioning
confidence: 99%
“…Gastroesophageal reflux disease (GERD) is the most significant clinical condition. GERD occurs as a result of both the decreased LES resting pressure, which allows an increased number of reflux events, and poor peristalsis, which delays acid clearance 16,17 . The complications of longstanding GERD include candida esophagitis, erosive esophagitis, esophageal stricture, Barret's esophagus, and aspiration.…”
Section: Discussionmentioning
confidence: 99%